The Etiology and Molecular Mechanism Underlying Smooth Muscle Phenotype Switching in Intimal Hyperplasia of Vein Graft and the Regulatory Role of microRNAs - Zhang, Dengshen; Cao, Yiran; Liu, Daxing; Zhang, Jian; Guo, Yingqiang (Frontiers in Cardiovascular Medicine, 2022)
Mounting evidence suggests that the phenotypic transformation of venous smooth muscle cells (SMCs) from differentiated (contractile) to dedifferentiated (proliferative and migratory) phenotypes causes excessive proliferation and further migration to the intima leading to intimal hyperplasia, which represents one of the key pathophysiological mechanisms of vein graft restenosis. In recent years, numerous miRNAs have been identified as specific phenotypic regulators of vascular SMCs (VSMCs), which play a vital role in intimal hyperplasia in vein grafts. The review sought to provide a comprehensive overview of the etiology of intimal hyperplasia, factors affecting the phenotypic transformation of VSMCs in vein graft, and molecular mechanisms of miRNAs involved in SMCs phenotypic modulation in intimal hyperplasia of vein graft reported in recent years.